Moss as Biomonitors of Vehicular Emissions Along Akure-Ilesa and Ife-Ibadan Roads in South Western Nigeria. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Vehicular emission is one of the major sources of pollution to the roadside vegetation and soil. Degree of pollution by vehicles depends on the traffic congestions on the road. Higher quantity of environmental pollution could pose several hazards to humans, animals and plants. This study investigated the impact of vehicular emission on lower plant (moss) along Akure-Ilesa and Ife-Ibadan roads. The study aims at: quantify the heavy metal (HM) load in the moss and compare the degree of pollution of Akure-Ilesa road with Ife-Ibadan road. Passive and active methods of biomonitoring was carried out using moss as indicator, digestion of the sample was done using aqua-regia method of digestion and the investigated metals: lead (Pb), chromium (Cr), cadmium (Cd), copper (Cu) and zinc (Zn) were analyzed with the use of Atomic Absorption Spectrophotometer (AAS). Results of these study reveal considerable quantity of the investigated metals present in the indicator material (moss) and it also shows that, Akure-Ilesa road have higher concentration of these metals than Ife-Ibadan road. It can be concluded from these study that vehicular emission contributed to the HM load of roadside lower plants. It is recommended that controlled vehicular emission systems be adopted to reduce emissions and improve fuel efficiency.